2019
DOI: 10.1111/ped.13837
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nutrition in the treatment of congenital diaphragmatic hernia

Abstract: Background The optimum enteral (EN) and parenteral nutrition (PN) regimens during acute management of congenital diaphragmatic hernia (CDH) remain unclear. We examined the effects of EN and PN on weight gain in CDH patients. Methods A multicenter retrospective cohort study of neonates with CDH (born 2006–2010; n = 105) who survived to discharge was conducted. Patients were divided as receiving PN ≥ or <50 kcal/kg/day at 1 week of age, and EN ≥ or <60 kcal/kg/day at 2 weeks of age. Changes in bodyweight at 30, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…GER, oral aversion, and allergies can also contribute to difficulties in enteral feeding [14,15]. We previously reported that EN and supportive PN in the acute phase were essential for weight gain during infancy [16]. Furthermore, increase in the energy requirement may be an underestimated factor [17].…”
Section: Discussionmentioning
confidence: 99%
“…GER, oral aversion, and allergies can also contribute to difficulties in enteral feeding [14,15]. We previously reported that EN and supportive PN in the acute phase were essential for weight gain during infancy [16]. Furthermore, increase in the energy requirement may be an underestimated factor [17].…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter study of 105 infants in Japan, Terui et al found that those who received ≥50 kcal/kg/d PN during the first week of life had significantly higher weight at age 60 and 90 days than those with <50 kcal/kg/d PN (60 days, 1.06 kg vs 0.71 kg [P = 0.006]; 90 days, 1.76 kg vs 1.41 kg [P = 0.004]). 13 One goal of nutrition support is to transition from PN to EN when appropriate, and the authors also analyzed the effect of EN in the second week of life. Similar to the results in their PN analysis, infants who received ≥60 kcal/kg/d EN by week 2 had significantly higher weight, by 23.4% and 22.5%, respectively, at 60 and 90 days than those with intake <60 kcal/kg/d (60 days, 4.31 kg vs 3.49 kg [P < 0.001]; 90 days, 5.16 kg vs 4.21 kg [P < 0.001]).…”
Section: Factors Related To Positive Outcomesmentioning
confidence: 99%
“…16 When preoperative feeding is not tenable, enteral nutrition (EN) should be introduced when bowel function, after surgical manipulation, returns. However, infants are often perceived to experience intolerance, which may be attributable to GER, 8 inconsistent intestinal motility related to analgesic medications, 13 or uncommonly, structural abnormalities within the gastrointestinal tract. 17 Some practitioners suggest aggressive strategies for managing GER, including medication, surgery, and feeding tube (FT) use, 16,17 whereas others point out that most infants will exhibit GER symptoms because of their liquid diet and postprandial supine positioning.…”
Section: Introductionmentioning
confidence: 99%
“…Terui et al . recently published the article, “Impact of nutrition in the treatment of congenital diaphragmatic hernia” in Pediatrics International . The conclusions of that article were as follows: the amount of enteral and parental nutrition is essential for weight gain during infancy in the acute phase of CDH management; an aggressive enteral nutrition strategy is recommended; and when CDH patients do not tolerate enteral nutrition, supportive parental nutrition is essential.…”
mentioning
confidence: 99%
“…In the nationwide, multicenter, retrospective observational study of neonatal CDH conducted by the Japanese Congenital Diaphragmatic Hernia Study Group reported by Terui et al . in this issue, the main message is that nutrition management is important for adequate bodyweight gain in infants with CDH . Although physical growth is an important issue in children, further research is required to establish an optimal nutritional strategy in order to improve neurodevelopmental outcomes.…”
mentioning
confidence: 99%